Wettbewerb: Fluch und/oder Segen? - Gebhard Kirchgässner (Aussenwirtschaft, 2011)
– In the philosophical literature, there exist rather positive but also rather negative evaluations of competition. It has, of course, positive and negative effects, for single individuals, for their moral behaviour, but also for the whole society.At least for the latter, the dynamic aspects are more relevant than the static ones. In connection with its negative effects it is frequently demanded that competition should be eliminated or at least restricted.This does often, however, not take into account its evolutionary nature; competition cannot just be switched on and off.Thus, the government has only limited options to make competition possible, to enhance or to suppress it. Because the suppression of competition always implies a restriction of individual liberty rights, it is not a trivial matter under which conditions and how such restrictions can be justified.
Keywords: H11; L40; 330; Competition; competition policy; discrimination; positional goods; limited government responsibility